Eficiência neuromuscular dos músculos vasto lateral e bíceps femoral em indivíduos com lesão de ligamento cruzado anterior - Aragão, Fernando Amâncio; Schäfer, Gabriel Santo; De Albuquerque, Carlos Eduardo; Vituri, Rogério Fonseca; Mícolis De Azevedo, Fábio [UNESP]; Bertolini, Gladson Ricardo Flor (Thieme, 2015)
Objective To analyze strength and integrated electromyography (IEMG) data in order to determine the neuromuscular efficiency (NME) of the vastus lateralis (VL) and biceps femoris (BF) muscles in patients with anterior cruciate ligament (ACL) injuries, during the preoperative and postoperative periods; and to compare the injured limb at these two times, using the non-operated limb as a control. Methods EMG data and BF and VL strength data were collected during three maximum isometric contractions in knee flexion and extension movements. The assessment protocol was applied before the operation and two months after the operation, and the NME of the BF and VL muscles was obtained. Results There was no difference in the NME of the VL muscle from before to after the operation. On the other hand, the NME of the BF in the non-operated limb was found to have increased, two months after the surgery. Conclusions The NME provides a good estimate of muscle function because it is directly related to muscle strength and capacity for activation. However, the results indicated that two months after the ACL reconstruction procedure, at the time when loading in the open kinetic chain within rehabilitation protocols is usually started, the neuromuscular efficiency of the VL and BF had still not been reestablished.
Neuromuscular efficiency of the vastus lateralis and biceps femoris muscles in individuals with anterior cruciate ligament injuries
Keywords: Anterior cruciate ligament; Biomechanics; Muscle fatigue